2016
DOI: 10.1088/2040-8978/18/8/080401
|View full text |Cite
|
Sign up to set email alerts
|

Rembrandt’s self-portraits

Abstract: This paper initially presents a demonstration of the ability of 17th century artists to achieve self-portrait projections using concave and flat mirrors, and subsequently develops a case for the likelihood of this technique being employed by Rembrandt van Rijn and other old master painters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In my opinion, a remarkable optical relation between Rembrandt's portraits and neuroendoscopic views is truly present. In a recent study conducted by the researchers F. O'Neill and S. Corner and published in the Journal of Optics in 2016, the authors provided further evidence that Rembrandt used lens and mirror technology to make his famous self-portraits [9]. Human figures in Rembrandt's portraits are located within the center of the composition and exposed to directional light that unveils their details.…”
Section: Rembrandt's Portraits and Neuroendoscopymentioning
confidence: 97%
See 1 more Smart Citation
“…In my opinion, a remarkable optical relation between Rembrandt's portraits and neuroendoscopic views is truly present. In a recent study conducted by the researchers F. O'Neill and S. Corner and published in the Journal of Optics in 2016, the authors provided further evidence that Rembrandt used lens and mirror technology to make his famous self-portraits [9]. Human figures in Rembrandt's portraits are located within the center of the composition and exposed to directional light that unveils their details.…”
Section: Rembrandt's Portraits and Neuroendoscopymentioning
confidence: 97%
“…Subsequently, some portions of the projected image are traced, altered, or completely ignored according to the painter's artistic vision [6,7]. Historical and artistic evidence made it currently wellknown that the French painter Jean-Auguste-Dominique Ingres (1780-1867) used a camera lucida to produce his portraits [6,8], and that Gerrit Dou (1613-1675), one of Rembrandt's students, employed grids, lenses, and mirrors to make his finely executed paintings [6,9].…”
Section: Optical Devices and Optical Realism In The Dutch Golden Age mentioning
confidence: 99%
“…He used the then-unknown in art practice mineral plumbonacrite in paint recipes. Scientists have revealed that the master created his self-portraits using a mirror system (O'Neill & Corner, 2016). The use of these technologies does not diminish the significance of Rembrandt's work in the history of fine art.…”
Section: Main Research Materialsmentioning
confidence: 99%